Children’s Inequity Aversion in Procedural Justice Context: A Comparison of Advantageous and Disadvantageous Inequity - Qiu, Xiaoju; Yu, Jing; Li, Tingyu; Cheng, Nanhua; Zhu, Liqi (Frontiers in Psychology, 2017)
There are two forms of unfairness widely studied in resource allocation settings: disadvantageous inequity (DI) in which one receives less than the partner and advantageous inequity (AI) in which one receives more than the other. We investigated children’s aversion to AI and DI in a procedural justice context. Children of 4-, 6-, and 8- years old were asked to spin a wheel(procedure) to decide how to allocate two different rewards with others. In each condition, they chose between a fair procedure providing equal chances for the two parties to get the bigger reward, and an unfair procedure(either a disadvantageous procedure in the DI condition, or an advantageous procedure in the AI condition). Results showed that children in the two younger age groups had a preference for the unfair procedure that would maximize their own profit in AI, but a greater aversion to the unfair procedure that would disadvantage them in DI. Eight-year-olds, however, had a greater preference for the fair procedure in AI than the 6-year-olds. In addition, the discrepancy between aversion to AI and DI disappeared in the 8-year-olds. The findings indicate children’s development of other-oriented concerns such as fairness concern and altruism in procedural justice, consistent with previous findings in distributive justice.